2012
DOI: 10.1080/13811118.2013.722055
|View full text |Cite
|
Sign up to set email alerts
|

Therapeutic Alliance and Change in Suicidal Ideation during Treatment in Integrated Primary Care Settings

Abstract: A strong therapeutic alliance is considered to be an essential factor for the effective assessment and management of suicidal patients; however, to date this has received little empirical attention. The current study evaluated the association of future change in suicidal ideation with therapeutic alliance during first appointments with primary care behavioral health consultants. The Behavioral Health Measure (BHM; Kopta & Lowery, 2002 ) and Therapeutic Bond Scale (TBS; CelestHealth Solutions, 2006) were compl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
22
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 36 publications
(26 citation statements)
references
References 24 publications
4
22
0
Order By: Relevance
“…The suicidal patients in this review addressed the vital importance of the therapeutic relationship in helping patients both feel safe and be safe. These findings are consistent with those of studies highlighting the therapeutic alliance in effective suicidal patient assessments and management [4547] and studies identifying the staff–patient relationship as important to patients’ feelings of safety [44, 48, 49]. Poor staff-patient relationships were found to play key roles in preventable suicides and were attributed to poor communication and relationship quality [50].…”
Section: Discussionsupporting
confidence: 83%
“…The suicidal patients in this review addressed the vital importance of the therapeutic relationship in helping patients both feel safe and be safe. These findings are consistent with those of studies highlighting the therapeutic alliance in effective suicidal patient assessments and management [4547] and studies identifying the staff–patient relationship as important to patients’ feelings of safety [44, 48, 49]. Poor staff-patient relationships were found to play key roles in preventable suicides and were attributed to poor communication and relationship quality [50].…”
Section: Discussionsupporting
confidence: 83%
“…Benefits from therapy, at least from the perspective of girls in our study, seem to derive from a trusted, empathetic relationship between the therapist and adolescent. Our findings compliment the results of previous studies of treatment post–suicide attempt, which support the moderating effect of a strong therapeutic alliance in reducing suicidal ideation (Bryan et al, 2012; Gysin-Maillart, Soravia, Gemperli, & Michel, 2017; Long, Manktelow, & Tracey, 2015).…”
Section: Discussionsupporting
confidence: 91%
“…Bryan et al (2012) used the Therapeutic Bond Scale to assess patient-rated evaluation of the treatment relationship, but found no association with the one suicide related item in the Behavior Health Measure-20 as outcome measure. In an earlier study we had reported that in a single assessment interview with patients who had attempted suicide, patient-rated therapeutic alliance measured with the Penn Helping Alliance Questionnaire HAq (Alexander & Luborsky, 1986) was increased when the interviewer used a narrative interviewing technique (Michel et al, 2004), based on a model of suicidal behavior as a goal-directed action (Michel & Valach, 1997 This approach stands in contrast to the traditional medical model, in which suicidal behavior is usually seen as a symptom of psychiatric disorder.…”
mentioning
confidence: 99%